Tethering Cells via Enzymatic Oxidative Crosslinking Enables Mechanotransduction in Non‐Cell‐Adhesive Materials (Adv. Mater. 42/2021). Issue 42 (19th October 2021) - Kamperman, Tom; Henke, Sieger; Crispim, João F.; Willemen, Niels G. A.; Dijkstra, Pieter J.; Lee, Wooje; Offerhaus, Herman L.; Neubauer, Martin; Smink, Alexandra M.; de Vos, Paul; de Haan, Bart J.; Karperien, Marcel; et al.
Abstract : Cell–Material Tethering Cells need to sense their environment in order to survive and function. In article number 2102660, Tom Kamperman, Jeroen Leijten, and co‐workers present an enzymatic crosslinking strategy that can tether non‐cell‐adhesive materials to cells. By targeting the cellular adhesome, this cell–material tethering method enables cell‐volume‐independent lineage programming of stem cells in engineered 3D microniches with controlled stiffness.